Empirical and diffusion models of rehydration process of differently dried pumpkin slices - A. Benseddik; A. Azzi; M.N. Zidoune; R. Khanniche; C. Besombes (Journal of the Saudi Society of Agricultural Sciences)
The present study investigated the rehydration kinetics of dried pumpkin slices issued from different drying operations, namely airflow drying (AFD), freeze-drying (FD), Vacuum Multi Flash Drying (VMFD) and Swell-drying (SD) which inserts Instant Controlled Pressure Drop (DIC) Texturing between two AFD stages (AFD + DIC + AFD). Rehydration process depends on dehydration methods. It has been noticed that the slowest rehydration process has been observed for AFD whilst VMFD, FD, and SD averred short rehydration time. Experimental rehydration curves were performed through empirical and diffusion models. Hence, it has been noticed that Weibull has provided the best rehydration fitting curve. In other hand, Fick's diffusion models were also used to describe kinetics of rehydration process. They were characterized by two effective diffusivity coefficients Deff1 and Deff2 for AFD and VMFD, and three effective diffusivity coefficients in the case of FD and SD (AFD + DIC + AFD). The temperature dependence of the diffusivity coefficients was also described by Arrhenius-type relationship, with adequate activation energy levels. Keywords: Rehydration, Empirical models, Diffusive models, Mass transfer, Pumpkin slices